A COMPARATIVE STUDY BETWEEN FOUR CORNERS STRATEGY AND GROUP WORK STRATEGY ON STUDENTS’ SPEAKING ABILITY - Ferri Yonantha (STAIN Sultan Abdurrahman Kepulauan Riau, 2018)
The present study is mainly aimed at comparing the use of Four Corners Strategy and Group Work Strategy on students’ speaking ability. It was encouraged by the low results of the students’ speaking ability. The research was carried out in a non-experimental form of comparative design that focused on quantitative approach. The total population of this study was 153 first semester students of State Islamic Higher College of Sultan Abdurrahman Kepulauan Riau in academic year 2017/2018. Meanwhile, the selected sample was 30 students (Class A) and 30 students (Class B). A speaking test was conducted after giving three meetings of treatment for both classes to measure their speaking ability. The results of the test were analyzed through compare means and t-test by using SPSS Statistics 20.0. As a result, it was found the mean score of the students taught by using Four Corners Strategy was higher than those taught by using Group Work Strategy. However, there was no significant difference between the use of Four Corners Strategy and Group Work Strategy on the students’ speaking ability improvement.